Duration of the hidden chromosome instability persistence in peripheral blood lymphocytes of persons occupationally exposed to ionizing radiation - Pilinskaya, M. A.; Dibskiy, S. S.; Dibskaya, Ye. B.; Shvayko, L. I.; Sushko, V. A. (Reports of the National Academy of Sciences of Ukraine, 2015)
With compatible use of tests "G2-bleomycin sensitivity assay" and two-term (48 and 100 h) cultivation of human peripheral blood lymphocytes, the voluntary cytogenetic examination of persons who have occupational contact with ionizing radiation is carried out. The results are compared with those obtained in a similar observation of the unexposed group. Principal differences between the groups in the manifestation and the dynamics of the hidden chromosome instability (HCI) in time are found. Its indicators were significantly higher in the occupational group. The possibility of the persistence of radiation-associated HCI in successive generations of human somatic cells with significant interindividual differences is established.